Inner Retinal Oxygen Delivery, Metabolism, and Extraction Fraction in Ins2(Akita) Diabetic Mice - Blair, Norman P. (Invest Ophthalmol Vis Sci, 2016)
PURPOSE: Retinal nonperfusion and hypoxia are important factors in human diabetic retinopathy, and these presumably inhibit energy production and lead to cell death. The purpose of this study was to elucidate the effect of diabetes on inner retinal oxygen delivery and metabolism in a mouse model of diabetes. METHODS: Phosphorescence lifetime and blood flow imaging were performed in spontaneously diabetic Ins2(Akita) (n = 22) and nondiabetic (n = 22) mice at 12 and 24 weeks of age to measure retinal arterial (O(2A)) and venous (O(2V)) oxygen contents and total retinal blood flow (F). Inner retinal oxygen delivery (DO(2)) and metabolism (MO(2)) were calculated as F ∗ O(2A) and F ∗ (O(2A) − O(2V)), respectively. Oxygen extraction fraction (OEF), which equals MO(2)/DO(2), was calculated. RESULTS: DO(2) at 12 weeks were 112 ± 40 and 97 ± 29 nL O(2)/min in nondiabetic and diabetic mice, respectively (NS), and 148 ± 31 and 85 ± 37 nL O(2)/min at 24 weeks, respectively (P < 0.001). MO(2) were 65 ± 31 and 66 ± 27 nL O(2)/min in nondiabetic and diabetic mice at 12 weeks, respectively, and 79 ± 14 and 54 ± 28 nL O(2)/min at 24 weeks, respectively (main effects = NS). At 12 weeks OEF were 0.57 ± 0.17 and 0.67 ± 0.09 in nondiabetic and diabetic mice, respectively, and 0.54 ± 0.07 and 0.63 ± 0.08 at 24 weeks, respectively (main effect of diabetes: P < 0.01). CONCLUSIONS: Inner retinal MO(2) was maintained in diabetic Akita mice indicating that elevation of the OEF adequately compensated for reduced DO(2) and prevented oxidative metabolism from being limited by hypoxia.